2013
DOI: 10.1111/acer.12288
|View full text |Cite
|
Sign up to set email alerts
|

Bioinformatics Analyses Reveal Age-Specific Neuroimmune Modulation as a Target for Treatment of High Ethanol Drinking

Abstract: Background Use of in silico bioinformatics analyses has led to important leads in the complex nature of alcoholism at the genomic, epigenomic, and proteomic level, but has not previously been successfully translated to the development of effective pharmacotherapies. In this study, a bioinformatics approach led to the discovery of neuroimmune pathways as an age-specific druggable target. Minocycline, a neuroimmune modulator, reduced high ethanol drinking in adult, but not adolescent, mice as predicted a priori.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
32
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 36 publications
(39 citation statements)
references
References 67 publications
6
32
1
Order By: Relevance
“…Further, in our investigations, we discovered that ethanol increases neuroinflammation in adult, but not adolescent mice (Kane et al, 2014). This is interesting in light of the observation that minocycline decreases alcohol consumption in adult but not adolescent mice supporting the concept that minocycline suppresses alcohol consumption by suppressing neuroinflammation (Agrawal et al, 2014). …”
Section: Therapiessupporting
confidence: 52%
“…Further, in our investigations, we discovered that ethanol increases neuroinflammation in adult, but not adolescent mice (Kane et al, 2014). This is interesting in light of the observation that minocycline decreases alcohol consumption in adult but not adolescent mice supporting the concept that minocycline suppresses alcohol consumption by suppressing neuroinflammation (Agrawal et al, 2014). …”
Section: Therapiessupporting
confidence: 52%
“…Decreased levels of proinflammatory cytokines in blood, for example, could translate to decreased cytokine release and signaling across the BBB, ultimately decreasing levels of inflammatory mediators in brain. We also note that other anti-inflammatory agents, such as minocycline, were proposed to reduce drinking in mice through direct central actions (Agrawal et al, 2014). It has been hypothesized that alcohol-induced inflammatory responses signal via peripheral-central positive-feedback cycles (Robinson et al, 2014).…”
Section: Discussionmentioning
confidence: 92%
“…Both adult and adolescent mice showed increased GFAP (glial fibrillary acidic protein) immunostaining, suggesting that astrocytes may play a role in the inflammatory response to ethanol (Kane et al, 2014). A bioinformatics analysis of adult mouse brains showed differential expression of TLR, JAK/STAT (Janus kinase/signal transducers and activators of transcription), MAPK (mitogen-activated protein kinase), T-cell, and chemokine signaling following a drinking in the dark paradigm, while these pathways were not overexpressed in adolescent mice (Agrawal et al, 2014). Also, minocycline, which has antiinflammatory properties, reduced drinking in adult but not in adolescent mice (Agrawal et al, 2014).…”
Section: Immune Regulation Of Ethanol Consumption and Ethanol Regumentioning
confidence: 99%
“…A bioinformatics analysis of adult mouse brains showed differential expression of TLR, JAK/STAT (Janus kinase/signal transducers and activators of transcription), MAPK (mitogen-activated protein kinase), T-cell, and chemokine signaling following a drinking in the dark paradigm, while these pathways were not overexpressed in adolescent mice (Agrawal et al, 2014). Also, minocycline, which has antiinflammatory properties, reduced drinking in adult but not in adolescent mice (Agrawal et al, 2014). However, other studies have reported opposite results.…”
Section: Immune Regulation Of Ethanol Consumption and Ethanol Regumentioning
confidence: 99%